Lithium Metal Penetration Induced by Electrodeposition through Solid Electrolytes: Example in Single-Crystal Li6La3ZrTaO12 Garnet. Issue 16 (1st January 2018) - Swamy, Tushar; Park, Richard; Sheldon, Brian W.; Rettenwander, Daniel; Porz, Lukas; Berendts, Stefan; Uecker, Reinhard; Carter, W. Craig; Chiang, Yet-Ming
Abstract : Solid electrolytes potentially enable rechargeable batteries with lithium metal anodes possessing higher energy densities than today's lithium ion batteries. To do so the solid electrolyte must suppress instabilities that lead to poor coulombic efficiency and short circuits. In this work, lithium electrodeposition was performed on single-crystal Li6 La3 ZrTaO12 garnets to investigate factors governing lithium penetration through brittle electrolytes. In single crystals, grain boundaries are excluded as paths for lithium metal propagation. Vickers microindentation was used to introduce surface flaws of known size. However, operando optical microscopy revealed that lithium metal penetration propagates preferentially from a different, second class of flaws. At the perimeter of surface current collectors smaller in size than the lithium source electrode, an enhanced electrodeposition current density causes lithium filled cracks to initiate and grow to penetration, even when large Vickers defects are in proximity. Modeling the electric field distribution in the experimental cell revealed that a 5-fold enhancement in field occurs within 10 micrometers of the electrode edge and generates high local electrochemomechanical stress. This may determine the initiation sites for lithium propagation, overriding the presence of larger defects elsewhere.